Falsafah Hidup Jawa dalam Naskah Sanguloro - Moh. Hasim (Jurnal Lektur Keagamaan, 2012)
The way of behaving of Javanese people that is based on the Javanese philosophy is stored in many manuscripts. However, the existence of manuscripts as the source of behavior among the Javanese is becoming alienated from their current lives because of the change of the lifestyles. This research tries to answer the question of what values are contained in the Sanguloro manuscript. Using philological approach, it is found that the manuscript contains the philosophy of harmony and customs that rule social life of the Javanese such as wise, helpful, humble and tolerant with others.